Desigualdad del Ingreso en el Perú: 1997-2017 - Cenas Rodríguez, Suni Areli (2019)
This study analyzes the impact of economic growth and educational level on income inequality in Peru during the period 1997-2017, using an econometric model of simple linear regression, which was annual statistical information of the World Bank (WB), Economic Commission for Latin America (ECLAC), National Institute of Statistics and Information Technology (INEI) and the Central Reserve Bank of Peru (BCRP), of these study variables. The content describes the evolution and the main characteristics of the income coefficient of GINI, the illiteracy rate and the PIB per capita in the study period, Indicators that were used for the development of the work. The results show a negative relationship between the GINI coefficient and the PBI percapita and a positive relationship between the GINI coefficient and the illiteracy rate. In quantitative terms, for each increase in PBI per capita in 1,000 soles, the GINI coefficient decreases by 0.000006345 points, as well as a decrease of 1% of the illiteracy rate the GINI coefficient decreases by 0.0073 points. This explains the relationship that the study variables have.